Associations between alcohol use and accelerated biological ageing. (12th October 2021) - Bøstrand, Sunniva M. K.; Vaher, Kadi; de Nooij, Laura; Harris, Matthew A.; Cole, James H.; Cox, Simon R.; Marioni, Riccardo E.; McCartney, Daniel L.; Walker, Rosie M.; McIntosh, Andrew M.; Evans, Kathryn L.; Whalley, Heather C.; et al.
Abstract: Harmful alcohol use is a leading cause of premature death and is associated with age‐related disease. Biological ageing is highly variable between individuals and may deviate from chronological ageing, suggesting that biomarkers of biological ageing (derived from DNA methylation or brain structural measures) may be clinically relevant. Here, we investigated the relationships between alcohol phenotypes and both brain and DNA methylation age estimates. First, using data from UK Biobank and Generation Scotland, we tested the association between alcohol consumption (units/week) or hazardous use (Alcohol Use Disorders Identification Test [AUDIT] scores) and accelerated brain and epigenetic ageing in 20, 258 and 8051 individuals, respectively. Second, we used Mendelian randomisation (MR) to test for a causal effect of alcohol consumption levels and alcohol use disorder (AUD) on biological ageing. Alcohol use showed a consistent positive association with higher predicted brain age (AUDIT‐C: β = 0.053, p = 3.16 × 10 −13 ; AUDIT‐P: β = 0.052, p = 1.6 × 10 −13 ; total AUDIT score: β = 0.062, p = 5.52 × 10 −16 ; units/week: β = 0.078, p = 2.20 × 10 −16 ), and two DNA methylation‐based estimates of ageing, GrimAge (units/week: β = 0.053, p = 1.48 × 10 −7 ) and PhenoAge (units/week: β = 0.077, p = 2.18x10 −10 ). MR analyses revealed limited evidence for a causal effect of AUD on accelerated brain ageing (β = 0.118, p = 0.044). However, this result should be interpreted cautiously as the significant effect was driven by a single genetic variant. We found no evidence for a causal effect of alcohol consumption levels on accelerated biological ageing. Future studies investigating the mechanisms associating alcohol use with accelerated biological ageing are warranted. Abstract : Harmful alcohol use is associated with age‐related disease. Recently, several biomarkers of biological ageing have been proposed, which may be clinically relevant. Here, using data from two large human cohorts, we found that alcohol use had consistent positive association with higher predicted brain and epigenetic age. Mendelian randomisation analyses revealed limited evidence for a causal effect of alcohol use disorder on accelerated brain ageing and no evidence for a causal effect of alcohol consumption levels on accelerated biological ageing.